Renogram in Children with Nephrotic Syndrome - I.G.N. Wila Wirya; H. Alatas; T. Tambunan; R. Sadeli; S. Budiman; E. Wijaya (Indonesian Pediatric Society, 1978)
Fifty children with nephrotic syndrome, aged 3 to 13 years, were studied for renogram patterns. Twenty-one cases had normal renograms; one case with bilateral and one with unilateral renal function. Seven cases showed bilateral renal impairment in both secretion and excretion phases. Impairment of excretion phase was found in 12 cases bilaterally and 8 unilaterally. None of them showed abnormality in the secretion phase alone. Eighteen out of 29 cases with abnormal renograms were studied further in remission states. The second renogram of these cases showed improvement to normal in 13 cases, two other cases still had impairment in the secretion and excretion phases, and the remaining 3 cases showed only impairment in the excretion phase. Ten healthy children as control had normal renograms. The correlation of clinical/laboratory findings and abnormal renograms patterns was discussed. Further studies on the use and limitation of the renograms in nephrotic syndrome in children are needed.